Evaluation of newly developed wearable ear canal thermometer, mimicking the application to activities on sports and labor fields - Issei Kato; Hironori Watanabe; Kei Nagashima (Journal of Physiological Sciences)
Abstract We evaluated the reliability of a newly developed wearable ear canal thermometer based on three different experiments, in which ear canal and rectal temperature (Tear and Trec, respectively) were simultaneously monitored. In Experiment 1, participants sat at 28 °C and 50% relative humidity (RH), during which fanning or 41 °C lower legs water immersion was conducted. In Experiment 2, participants conducted a 70-min treadmill exercise (4 km/h, 0.5% slope) at 35 °C and 50% RH with intermittent fanning. In Experiment 3, participants completed a 20 min treadmill exercise (6 km/h, 5% slope) at 35 °C and 65% RH. Bland–Altman analysis for Tear and Trec showed the difference of − 0.2–0.3 °C and the limit of agreement of the mean ± 0.3–0.6 °C. The intraclass correlation coefficient was 0.44–0.83. The results may suggest that the ear canal thermometer is useful to assess core body temperature in sports and/or labor fields.